Funções elíticas simétricas e aplicações em superfícies mínimas - Hancco, Alvaro Julio Yucra (2010)
In 1989, H.Karcher elaborated a method for the construction of minimal surfaces, denominated reverse construction method given in [10]. In that work it was rewritten the theory of elliptic functions using an approach more geometrical than analytical. This allows to better control the behavior and the image values of those functions, making it easier his application in minimal surfaces. In this master s thesis, we will present basic tools of the theory of symmetric elliptic functions, describing explicitly the symmetric ℘-Weierstraß and the function γ, that will be applied in the reverse construction method for an example of minimal surface.